Design and Implementation of Voltage Source Inverter Using Sinusoidal Pulse Width Modulation Technique to Drive A Single-Phase Induction Motor - Shneen, Salam Waley; Abdullah, Zainab B.; Dakheel, Hashmia S. (International Journal of Robotics and Control Systems, 2024)
A study is underway under the title, Design and implementation of voltage source inverter using sinusoidal pulse width modulation technique to drive a single-phase induction motor. The objectives of the study can be achieved by building a simulation model for a single-phase full-wave inverter consisting of four IGBT transistors. The inverter converts a direct voltage of 220 volts from the power source connected to the inverter input to an alternating voltage of 220 volts RMS. A 10-ohm resistive load is fed to the inverter output. In the first test, a square wave is generated as a result of operating the inverter in the first mode, as a result of activating two electronic switches that give the value of the voltage wave to the load, while the second mode gives the negative voltage with an interval of ten milliseconds for each mode, i.e., at a frequency of 50 Hz for twenty milliseconds for the square wave generated at the inverter output. The other model uses sinusoidal pulse width modulation technique to remove harmonics and control the inverter output by opening and closing electronic switches, which leads to removing some harmonics. The third model depends on adding a filter to obtain the basic wave and get rid of the rest of the harmonics, which results in generating a sine wave. After obtaining an inverter model that converts 220 volts direct voltage to 220 volts alternating voltage RMS as a first stage, the second stage is to feed a single-phase induction motor and operate it under test conditions that include a no-load condition, i.e., zero torque, a constant load condition, i.e., 1 Newton-meter torque, and finally a variable load condition, which is similar to many applications such as a fan, pump, etc. From the simulation results, we can say that the system is effective in operating the induction motor at the specified speed (1430 rpm) after providing the specified electrical quantities, a frequency of 50 Hz, and a voltage of 220 volts alternating voltage RMS.